2020
DOI: 10.1002/cam4.3362
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of rituximab and HIV on the survival of Ontario patients with diffuse large B‐cell lymphoma

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…Besides, we also found that HIV-associated features, which include CD4 cell count did not affect prognosis of HIV-associated BL. Habbous et al [21] also found that HIV status did not affect prognosis for patients with DLBCL receiving R-CHOP in a general population.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Besides, we also found that HIV-associated features, which include CD4 cell count did not affect prognosis of HIV-associated BL. Habbous et al [21] also found that HIV status did not affect prognosis for patients with DLBCL receiving R-CHOP in a general population.…”
Section: Discussionmentioning
confidence: 92%
“…Habbous et al. [ 21 ] also found that HIV status did not affect prognosis for patients with DLBCL receiving R‐CHOP in a general population.…”
Section: Discussionmentioning
confidence: 99%
“…In this retrospective study, we investigated predictors of survival for HIV-associated B-cell lymphoma. Whether HIV status impairs outcomes of DLBCL patients treated with standard immunochemotherapy in the HAART era remains controversial, 23 - 25 which means that prognostic factors might differ between these 2 groups. By RNA-seq, Fedoriw et al 26 identified a strong contribution of HIV status to DLBCL gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Основная характеристика ПВЛ -опухолевые выпоты в полостях тела без обнаруживаемых опухолевых масс. Для данных нозологических лимфом Национальная всеобщая онкологическая сеть (NCCN, США) рекомендует общий терапевтический подход (R-EPOCH, R-CHOP) с профилактикой поражения ЦНС метотрексатом и цитарабином с активным наблюдением на момент развития инфекционных осложнений [20,[22][23][24][25][26].…”
Section: первичная выпотная лимфомаunclassified